Tregitopes Improve Asthma by Promoting Highly Suppressive and Antigen-Specific Tregs - Dembele, Marieme; Tao, Shao; Massoud, Amir H.; Miah, S. M. Shahjahan; Lelias, Sandra; De Groot, Anne S.; Mazer, Bruce D. (Frontiers in Immunology, 2021)
Tregitopes (T regulatory epitopes) are IgG-derived peptides with high affinity to major histocompatibility complex class II (MHCII), that are known to promote tolerance by activating T regulatory cell (Treg) activity. Here we characterized the effect of IgG Tregitopes in a well-established murine model of allergic asthma, demonstrating in vivo antigen-specific tolerance via adoptive transfer of Tregitope-and-allergen-activated Tregs. Asthma is a heterogeneous chronic inflammatory condition affecting the airways and impacting over 300 million individuals worldwide. Treatment is suppressive, and no current therapy addresses immune regulation in severely affected asthmatics. Although high dose intra-venous immunoglobulin (IVIg) is not commonly used in the asthma clinic setting, it has been shown to improve severe asthma in children and in adults. In our laboratory, we previously demonstrated that IVIg abrogates airway hyperresponsiveness (AHR) in a murine model of asthma and induces suppressive antigen-specific T-regulatory cells. We hypothesized that IgG-derived Tregitopes would modulate allergic airway disease by inducing highly suppressive antigen-specific Tregs capable of diminishing T effector cell responses and establishing antigen-specific tolerance. Using ovalbumin (OVA-) and ragweed-driven murine models of allergic airway disease, we characterized the immunoregulatory properties of Tregitopes and performed Treg adoptive transfer to OVA- and ragweed-allergic mice to test for allergen specificity. Treatment with Tregitopes attenuated allergen-induced airway hyperresponsiveness and lung inflammation. We demonstrated that Tregitopes induce highly suppressive allergen-specific Tregs. The tolerogenic action of IgG Tregitopes in our model is very similar to that of IVIg, so we foresee that IgG Tregitopes could potentially replace steroid-based treatment and can offer a synthetic alternative to IVIg in a range of inflammatory and allergic conditions.